Having No Son Impacts Unmet Need for Family Planning: Evidence Based on Demographic Health Survey Data of Bangladesh - Rummana, Shahrukh; Rahman, Md. Morshadur; Mallick, Taslim Sazzad (Health Nexus, 2024)
Unmet need for family planning, not only lower the satisfied demand of contraceptive use, but also elevate maternal and child death of a country. In order to achieve the targets of sustainable development goal on satisfied demand for family planning (FP), it is essential to reduce the current rate of unmet need for FP in Bangladesh. This study attempted to explore whether son preference increases the rate of unmet for FP after adjusting the effects of other potential confounders. This study used nationally representative data of 2014 Bangladesh Demographic Health Survey (BDHS). A total of 12031 women were selected after removing the missing observations. Bivariate analyses were carried out using chi-square tests to estimate unadjusted effects of several factors on unmet need for FP, while a logistic regression model was used for the estimation of adjusted effects. The odds of unmet need for FP was 22% higher for the couples having no son (CI: 1.05-1.43; p-value = 0.01). Significantly higher unmet need for FP was also found for the couples having more than 7 years of age gap, having 4 or more living children, if none of them were educated, living in rural area, if wives were not working, if wives did not have NGO membership, if they did not receive any contraceptives while visited by FP workers, if wives were not empowered and if they were not living together. Along with the factors that are known to influence unmet need for FP in the developing countries, this study reveals that unmet need for FP is also affected by son preference in Bangladesh.